(untitled) (Journal of Social Sciences Review, 2023)
This paper is purposely prepared to explore the significance of marketing intelligence in primary marketing development, specifically with regard to SWOT analysis. It also aims to identify common issues associated with SWOT analysis and propose a systematic approach to addressing them. This topic has been widely discussed in the research field, and while there have been previous efforts to address it, there is still potential for further exploration and development. The paper is based on a comprehensive literature review, which suggests that pre-job assessment can have a positive impact on the effectiveness of primary marketing planning by evaluating the SWOT analysis. Optimistically, this paper will help marketing managers understand the standing of marketing intelligence, advertising vision and pre-job valuation in evolving operative primary promotion plans.